The main idea of this study was to evaluate the influence of export to regional economic development. The cinnamon was superior export commodity of Kerinci regency, which support to regional economic development. The purpose of this study was to analyze cinnamon sector effect to regional economic development of Kerinci Regency of Jambi and to analyse cinnamon price integration on farmers and export corporation level. The study used qualitative and quantitative methods. The data consisted of p - Askar Jaya; Ernan Rustiadi; Isang Gonarsyah; Deddy S. Bratakusumah; Bambang Juanda (Forum Pasca Sarjana, 2009)
The main idea of this study was to evaluate the influence of export to regional economic development. The cinnamon was superior export commodity of Kerinci regency, which support to regional economic development. The purpose of this study was to analyze cinnamon sector effect to regional economic development of Kerinci Regency of Jambi and to analyse cinnamon price integration on farmers and export corporation level. The study used qualitative and quantitative methods. The data consisted of primary and secondary data. The primary data were collected from survey and interview with respondents, such as farmers, traders, cinnamon entrepreneurs, local government staffs and other informants. The secondary data were collected from Badan Pusat Statistik, Central Bank of Indonesia and FAOSTAT. The analysis model consisted of descriptive model, input-output model, OLS regression combined with co-integration model and error correction model (ECM). The results showed that the cinnamon had low correlation to support regional economic development and indicate regional leakage. The farmers’ level price had no significant integration to export corporation price. Increasing quality and industry processing development is the most important strategy. Key words: cinnamon, sectoral linkages, price integration, regional economics, agroindustry processing